Interface Composition with Ethnomusicology: A Perspective Materialized in Five Contemporary Pieces (Orfeu, 2020)
This work presents discussions about the compositional process of five works composed from an interface perspective between composition and ethnomusicology, based on a study of Candomblé music associated to compositional notions from its rhythmic processes. Supported in theories of rhythm (COOPER and MEYER, 1960; KRAMER, 1988; and HESTY, 1997), in the literature on Candomblé music and African music (LÜHNING, 1990; KUBIK, 2010;BRANDA LACERDA, 2014; and AGAWU, 2016), and through an ethnographic approach, five rhythmic processes were identified, conceptualized and exemplified: 1) rhythmic resignification; 2) rhythmic dissociation, 3) rhythmic sintonization; 4) rhythmic suspension; and 5) rhythmic sublimation. These are problematized in the artistic production in question, through an adaptive impulse related to the large imagery of contemporary concert music, in its temporal, textural, gestural and formal dimensions.
Keywords: Composition; Contemporary concert music; Candomblé; Rhythmic processes; Ethnomusicology